2019
DOI: 10.1177/0271678x19848505
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic lesion growth in acute stroke: Water uptake quantification distinguishes between edema and tissue infarct

Abstract: Infarct growth from the early ischemic core to the total infarct lesion volume (LV) is often used as an outcome variable of treatment effects, but can be overestimated due to vasogenic edema. The purpose of this study was (1) to assess two components of early lesion growth by distinguishing between water uptake and true net infarct growth and (2) to investigate potential treatment effects on edema-corrected net lesion growth. Sixty-two M1-MCA-stroke patients with acute multimodal and follow-up CT (FCT) were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 38 publications
6
26
0
Order By: Relevance
“…15 Consequently, there is an urgent need for reliable imaging biomarkers that strongly correlate with time-dependent ischemic edema formation and functional outcome after treatment. 3 Our finding that increased ischemic lesion NWU strongly predicts functional outcome are line with prior studies. 2,3,9,10,15 Interestingly, we found that favorable TLC and lower ischemic lesion NWU were strong predictors of good functional outcome regardless of CTA collateral status.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…15 Consequently, there is an urgent need for reliable imaging biomarkers that strongly correlate with time-dependent ischemic edema formation and functional outcome after treatment. 3 Our finding that increased ischemic lesion NWU strongly predicts functional outcome are line with prior studies. 2,3,9,10,15 Interestingly, we found that favorable TLC and lower ischemic lesion NWU were strong predictors of good functional outcome regardless of CTA collateral status.…”
Section: Discussionsupporting
confidence: 92%
“…3 Our finding that increased ischemic lesion NWU strongly predicts functional outcome are line with prior studies. 2,3,9,10,15 Interestingly, we found that favorable TLC and lower ischemic lesion NWU were strong predictors of good functional outcome regardless of CTA collateral status. The uncoupling of CTA collateral robustness, despite being an independent predictor of final infarct volume, from TLC as a predictor of functional outcome in AIS-LVO patients has been described before.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Broocks et al have developed a densitometry based NWU measure that relies on the relationship of increasing lesion volume due to water content and the associated density reduction on NCCT (18). Due to the increased reliability to distinguish EV from within the ischemic lesion compared to the global imaging markers and its easy applicability to widely available NCCT scans, this method was utilized in this study (7,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%